Emergence of undifferentiated urothelial carcinoma after pembrolizumab treatment for patient with invasive urothelial bladder cancer: A case report - Moto Hasegawa; Go Hasegawa; Yohei Ikeda; Noboru Hara; Tsutomu Nishiyama (SAGE Open Medical Case Reports, 2020)
An 83-year-old man received pembrolizumab treatment after anticancer chemotherapy with gemcitabine and cisplatin for advanced bladder cancer. Pathological findings revealed invasive urothelial carcinoma with squamous differentiation before treatment. After seven courses of pembrolizumab treatment, the tumor disappeared. After 15 courses of the treatment, the tumor regrew. Pathological findings revealed invasive undifferentiated urothelial carcinoma consisting of relatively small tumor cells of the same size as lymphocytes, negative for neuroendocrine markers. Programmed death-ligand 1 expressions in tumor tissue changed from positive before treatment to negative after pembrolizumab treatment.